The Best American Short Stories, 1996 : selected from U.S. and Canadian magazines - Wideman, John Edgar; Kenison, Katrina (Boston : Houghton Mifflin, 1996)
A compilation of twenty-four American short stories by authors such as Mary Gordon, Robert Olen Butler, Alice Adams, and Jamaica Kincaid. Includes a list of 100 additional notable stories from 1995.
Foreword -- Introduction / John Edgar Wideman -- Complicities / Alice Adams -- Fires / Rick Bass -- Driving the heart / Jason Brown -- Jealous husband returns in form of parrot / Robert Olen Butler -- The eve of the Spirit Festival / Lan Samantha Chang -- Fitting ends / Dan Chaon -- The silver screen / Peter Ho Davies -- Ysrael / t
Keywords: Short stories, American; American fiction -- 20th century; Short stories, Canadian; Canadian fiction -- 20th century